2020
DOI: 10.1186/s12935-020-01207-w
|View full text |Cite
|
Sign up to set email alerts
|

LBX2-AS1 up-regulated by NFIC boosts cell proliferation, migration and invasion in gastric cancer through targeting miR-491-5p/ZNF703

Abstract: Background: The crucial role of long non-coding RNAs (lncRNAs) has been certified in human cancers. The lncRNAs with abnormal expressions could act as tumor inhibitors or oncogenes in the advancement of tumors. LBX2-AS1 was once reported to accelerate esophageal squamous cell carcinoma. Nonetheless, its function in gastric cancer (GC) remained a riddle. Methods: RT-qPCR was used to examine the expression of NFIC/LBX2-AS1/miR-491-5p/ZNF703 in GC cell lines. The functions of LBX2-AS1 in GC were appraised by colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…Further clarification of the mechanism and role of different miRNAs in BC is of great significance for diagnosis and targeted therapy. MiR-491-5p, as a member of the miRNA family with regulatory oncogenes, can prevent the processes of multiple cancers, including bladder cancer, 14 non-Small cell lung cancer, 15 lung adenocarcinoma, 16 acute lymphoblastic leukemia, 17 gastric cancer, 18 and so on. However, the role and mechanism of miR-491-5p in BC progression are completely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Further clarification of the mechanism and role of different miRNAs in BC is of great significance for diagnosis and targeted therapy. MiR-491-5p, as a member of the miRNA family with regulatory oncogenes, can prevent the processes of multiple cancers, including bladder cancer, 14 non-Small cell lung cancer, 15 lung adenocarcinoma, 16 acute lymphoblastic leukemia, 17 gastric cancer, 18 and so on. However, the role and mechanism of miR-491-5p in BC progression are completely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, overexpression of SPAG5 gene significantly promoted the viability, proliferation, migration, invasion and inhibition of apoptosis of ESCC cells (Figure 4 and Figure 5). It is reported that cell proliferation, apoptosis, migration and invasion are closely related to the changes of the related protein expression [11,15,16,19,24]. The expression of Caspase-3, Ki67 and VEGF in tumor tissues is closely related to the proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation, apoptosis, migration and invasion of tumor cells are the necessary stages of tumor occurrence and development [2,11,15,16,19]. Drug resistance is one of the important reasons for the low survival rate of cancer patients [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of MMP9 by miR-491-5p has been implicated in lowering metastasis and tissue invasion in hepatocellular carcinoma and osteosarcoma [129,130]. MiR-491-5p also decreases cellular proliferation and motility in neoplastic models through activity on other gene targets, but further investigation of its effects on MMP activity during impaired wound healing is required [131,132]. Within placental tissue, miR-491-5p inhibits MMP9 activity, leading to lower trophoblast invasion and higher rates of pre-eclampsia [133].…”
Section: Ecm Remodeling By Mirna-491-5p In Pressure Ulcersmentioning
confidence: 99%